2002
DOI: 10.1038/ng840
|View full text |Cite
|
Sign up to set email alerts
|

CEACAM1 regulates insulin clearance in liver

Abstract: We hypothesized that insulin stimulates phosphorylation of CEACAM1 which in turn leads to upregulation of receptor-mediated insulin endocytosis and degradation in the hepatocyte. We have generated transgenic mice over-expressing in liver a dominant-negative, phosphorylation-defective S503A-CEACAM1 mutant. Supporting our hypothesis, we found that S503A-CEACAM1 transgenic mice developed hyperinsulinemia resulting from impaired insulin clearance. The hyperinsulinemia caused secondary insulin resistance with impai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
254
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 227 publications
(275 citation statements)
references
References 42 publications
13
254
0
1
Order By: Relevance
“…It was shown that the CEACAM1 protein exhibits antiproliferative properties in carcinomas of colon (24) and prostate (25). Additional data support the central involvement of CEACAM1 in angiogenesis (26), metastasis (27), and insulin clearance (28). CEACAM1 also has a role in the modulation of innate and adaptive immune responses.…”
Section: Inhibition Of Human Tumor-infiltrating Lymphocyte Effector Fmentioning
confidence: 73%
“…It was shown that the CEACAM1 protein exhibits antiproliferative properties in carcinomas of colon (24) and prostate (25). Additional data support the central involvement of CEACAM1 in angiogenesis (26), metastasis (27), and insulin clearance (28). CEACAM1 also has a role in the modulation of innate and adaptive immune responses.…”
Section: Inhibition Of Human Tumor-infiltrating Lymphocyte Effector Fmentioning
confidence: 73%
“…CEACAM1 is expressed in epithelia and leukocytes in addition to the endothelia of small angiogenic blood vessels. Furthermore, CEACAM1 is involved in the insulin clearance in the liver (Poy et al, 2002). It was shown that CEACAM1 isoforms are expressed on the surface of Tcells upon activation and are involved in the regulation of Th1-mediated inflammation (Iijima et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The inhibitory activity of the long cytoplasmic domain is most likely mediated by the binding of Src homology protein-1/2 (SHP-1/2) via its Src homology 2 domains to the phosphorylated ITIM (4,8). A critical Ser residue (S-503 in rat CEACAM1-4L) has also been identified in the long cytoplasmic domain that controls signaling via the insulin receptor in rat hepatocytes (9,10). The 14-aa-short cytoplasmic domain lacks Tyr residues, but can be phosphorylated by protein kinase C on Ser and Thr residues (11) and binds calmodulin (CaM) (11) and both actin and tropomyosin (12).…”
mentioning
confidence: 99%